A RESPON KEMOTERAPI FLUDARABINE PADA HAIRY CELL LEUKEMIA - Tandya, Renny (Jurnal Ilmiah Kesehatan Media Husada, 2023)
HCL is part of a rare B-cell lymphoproliferative disorder and is a subtype of Chronic Lymphocytic Leukemia. It is characterized by progressive pancytopenia, splenomegaly, and bone marrow hypercellularity. Patients often come because of abnormal complete blood count results or complications such as infection. This case report explains a case of a 41-year-old woman who had recurrent shortness of breath and cough as symptoms, where the patient had a history of acute myeloblastic leukemia (AML) with non-routine fludarabine chemotherapy. After receiving treatment and underwent further investigations in the form of peripheral blood smear and bone marrow aspiration examination, it was found that the patient had hairy cell leukemia. Fludarabine was given to the patient and it is reported to give effect partial remission (based on last bone marrow aspiration) along with pancytopenia as a clinical manifestation from myelosuppression as a side effect for long-term used fludarabine. HCL is part of a rare B-cell lymphoproliferative disorder and is a subtype of Chronic Lymphocytic Leukemia. It is characterized by progressive pancytopenia, splenomegaly, and bone marrow hypercellularity. Patients often come because of abnormal complete blood count results or complications such as infection. This case report explains a case of a 41-year-old woman who had recurrent shortness of breath and cough as symptoms, where the patient had a history of acute myeloblastic leukemia (AML) with non-routine fludarabine chemotherapy. After receiving treatment and underwent further investigations in the form of peripheral blood smear and bone marrow aspiration examination, it was found that the patient had hairy cell leukemia. Fludarabine was given to the patient and it is reported to give effect partial remission (based on last bone marrow aspiration) along with pancytopenia as a clinical manifestation from myelosuppression as a side effect for long-term used fludarabine.